The impact of eHealth on relationships and trust in primary care: a review of reviews - Ramachandran, Meena; Brinton, Christopher; Wiljer, David; Upshur, Ross; Gray, Carolyn Steele (BMC family practice, 2023)
Background Given the increasing integration of digital health technologies in team-based primary care, this review aimed at understanding the impact of eHealth on patient-provider and provider-provider relationships. Methods A review of reviews was conducted on three databases to identify papers published in English from 2008 onwards. The impact of different types of eHealth on relationships and trust and the factors influencing the impact were thematically analyzed. Results A total of 79 reviews were included. Patient-provider relationships were discussed more frequently as compared to provider-provider relationships. Communication systems like telemedicine were the most discussed type of technology. eHealth was found to have both positive and negative impacts on relationships and/or trust. This impact was influenced by a range of patient-related, provider-related, technology-related, and organizational factors, such as patient sociodemographics, provider communication skills, technology design, and organizational technology implementation, respectively. Conclusions Recommendations are provided for effective and equitable technology selection, application, and training to optimize the impact of eHealth on relationships and trust. The review findings can inform providers' and policymakers' decision-making around the use of eHealth in primary care delivery to facilitate relationship-building. Keywords: eHealth, Technology, Primary care, Relationships, Trust